Head and Neck Cancer Management - Shams, Salima (Asian Pacific Journal of Cancer Care, 2023)
Head and Neck Cancer (HNC) is a broad category of cancer, comprises of cancer that origin into oral cavity, pharynx, larynx, sinuses and salivary gland. Majority of oral cancer cases reported in Pakistan are metastatic to Head and Neck and are with morphology of squamous cell carcinoma. Locally advance, un-resectable tumors are treated with systemic therapies. Commonly prescribe systemic therapies includes chemotherapy and targeted therapy. However, chemotherapy is the most prescribed systemic therapy because of advance presentation of cases with the morphology of Squamous cell carcinoma. Cisplatin and Carboplatin are drug of choice in HNC treatment. Chemotherapy treatment result in many toxicities such as nausea-vomiting, nephrotoxicity, cystitis, diarrhea, mucositis, ototoxicity, myelosuppresion, allergic reaction and others. These side-effects could be overcome through pharmacological and non-pharmacological interventions.